The Psychosocial Challenges Faced by Women With High-Risk Pregnancies - Okta Zenita Siti Fatimah; Seventina Nurul Hidayah (Jurnal Kesehatan, 2023)
High-risk pregnancies are often associated with higher psychological and emotional challenges for expectant mothers. This qualitative study aimed to explore the psychosocial challenges faced by women with high-risk pregnancies in the Kudaile Slawi neighborhood. The research utilized in-depth interviews with ten women who were identified as having high-risk pregnancies. The findings reveal several significant psychosocial challenges these women encountered during their pregnancies, including heightened anxiety and fear, emotional distress, feelings of vulnerability, and concerns about the well-being of their unborn babies. Participants also highlighted the importance of social support, particularly from family members and healthcare providers, in coping with these challenges. The study underscores the need for tailored psychosocial support and counseling services for women with high-risk pregnancies to address their unique emotional and psychological needs. Additionally, it emphasizes the importance of healthcare providers recognizing and addressing these challenges to improve the overall maternal and fetal outcomes in such cases. Keywords: High-risk pregnancy, psychosocial challenges, maternal well-being, emotional distress, social support.